Pengaruh Tata Kelola Perusahaan Terhadap Pengungkapan Risiko Perusahaan Pada Perusahaan Sektor Industri Barang Konsumen Primer Yang Terdaftar Di Bei Tahun 2020-2022 - Hidayat, Solikhul; Zannuba Habibah Salsabila (Jurnal Rekoginisi Ekonomi Islam, 2024)
One of the information that investors consider before investing is information about risk and risk control management contained in the company's annual report. This study aims to obtain empirical evidence on the influence of corporate governance which includes institutional ownership structure, managerial ownership structure, audit committee, and the proportion of independent board of commissioners on corporate risk disclosure in companies in the primary consumer goods industry sector listed on the Indonesia Stock Exchange in 2020-2022. The sampling technique in this study used purposive sampling techniques with the number of samples obtained by 37 companies and obtained observational data as many as 111 data. Data processing using multiple regression with SPSS 20. The results showed that institutional ownership structure and the audit committee has no significant effect on the company's risk disclosure. The managerial ownership structure has a significant negative effect on the company's risk disclosure and the proportion of independent board of commissioners has a significant positive effect on the company's risk disclosure variables.